Pesan-Pesan Dakwah dalam Musik Gambus Revolusioner Al-Badar - Nurul Abrari; A.Khairuddin (Fakultas Dakwah Universitas Ibrahimy, 2022)
Da’wah is a call or invitation for conversion or an attempt to change the situation to a better and perfect situation, both to the individual and to society. One of the media or elements that can be used for preaching is the art of music. One of the important elements in the cultural system is art. To re- member religious advice that comes from the Qur’an and Hadith, through Al-Badar Revolutionary gambus music, religious advice will be more easily accepted, because the song lyrics offer rhythmic notation and depth of meaning that can make the heart lulled in its strains.Researchers here examine the message of da’wah in the music of Al-Badar Revolutionary Gambus. To find a new theory and answer the researcher’s anxiety about the above theme, the researcher first digs up the data by obser- ving, interviewing and documenting the objects related to the research.From the data obtained, the results of this study indicate that Al-Badar Revolutionary Gambus Music is able to make music as an intermediary (media) to convey da’wah in this music. The message content of al-Badar gambus mu- sic contains a message of da’wah that invites goodness and contains the values of Islamic teachings. Both the message is worth the category of aqidah, morality and shari’ah.